1982
DOI: 10.1002/neu.480130104
|View full text |Cite
|
Sign up to set email alerts
|

Histamine: Correlative studies in nucleus accumbens

Abstract: The role of histamine as a neurotransmitter has been the subject of considerable controversy. Recent evidence suggests it to be involved in such complex activities as arousal and affect. The purpose of the present study is to examine the possible source, function, and pharmacology of histamine in the nucleus accumbens, an area of the brain also implicated in complex activities such as affect. The anatomical studies suggest that the most probable source of the histamine in nucleus accumbens is the complex regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The cell clusters in the rat Acb were first studied in detail by Herkenham et al (1984), although some anatomical reports on the rat Acb nucleus were found in the older literature (Chronister et al, 1982). Herkenham et al (1984) reported that the cell clusters were composed of densely packed medium-sized spiny neurons, were distinguished from the islands of Calleja of much smaller granule cells, and were only poorly innervated by the inputs from the thalamic nuclei or ventral tegmental area.…”
Section: Cell Clusters In the Ventral Striatum And Lssmentioning
confidence: 98%
“…The cell clusters in the rat Acb were first studied in detail by Herkenham et al (1984), although some anatomical reports on the rat Acb nucleus were found in the older literature (Chronister et al, 1982). Herkenham et al (1984) reported that the cell clusters were composed of densely packed medium-sized spiny neurons, were distinguished from the islands of Calleja of much smaller granule cells, and were only poorly innervated by the inputs from the thalamic nuclei or ventral tegmental area.…”
Section: Cell Clusters In the Ventral Striatum And Lssmentioning
confidence: 98%
“…It was thus clear that histamine could regulate some aspects of the striatal circuit but there were still many questions outstanding. These included the potential modulation of the thalamic projection to the striatum, which forms the other major excitatory glutamatergic afferent to the striatum ( Smith et al., 2014 ), and the potential differential modulation of the two main types of striatal MSN (see Table 1 ) Indeed, several in vivo studies of the activity patterns in the striatum came to different conclusions on the effect of histamine on striatal neural activity with both increases ( Sittig and Davidowa, 2001 ) and decreases ( Chronister et al., 1982 ) in neural activity reported upon histamine infusion in vivo . Most likely these conflicting results result from the inherent heterogeneity of striatal neurons.…”
Section: Histamine and The Striatummentioning
confidence: 99%
“…The accumbens was chosen for several reasons; firstly, substantial levels of histamine have been measured in this regior (Bennett et al, 1983) and more recently, immunohistochemical studies have suggested a histaminergic pathway arising from cell bodies in the posterior hypothalamus and terminating in the accumbens (Steinbusch & Mulder, 1985;Pollard & Schwartz, 1987). Thirdly, histamine agonists have been shown to alter neuronal firing in rabbit accumbens and activation of adenylate cyclase in this region appears to be mediated by both H1and H2-receptors (Chronister et al, 1982). Finally, it is well established that the nucleus accumbens plays an important role in the control of motor activity (Mogenson et al, 1980).…”
Section: Introductionmentioning
confidence: 99%